Pendidikan Agama Islam Berbasis Multikultural dalam Menanggulangi Terorisme dan Konflik Sosial - Saharuddin; Muhammad Aidul; Muhammad Aditia (Jurnal Pendidikan Kreatif, 2024)
This article discusses Islam education which is multicultural in nature and aims to resolve social conflicts and terror. The purpose of this study is to understand Islamic teaching principles and practices based on multiculturalism in order to address social injustice and conflict. Given the numerous social conflicts resulting from the kekerasan in Indonesia, it is hoped that Islamic education with a multicultural curriculum will be able to provide solutions for any problems that may arise. The goal of multicultural Islamic education is to foster empathy and self-improvement in order to resolve interpersonal conflicts. This study employs a methodological approach by gathering data through relevant literature, journal articles, and study books. Because of this, it is believed that Islamic education can help students develop their morality and character through educational activities including character education and character development workshops.